2017
DOI: 10.1080/14737175.2018.1414601
|View full text |Cite
|
Sign up to set email alerts
|

Dysautonomia in the pathogenesis of migraine

Abstract: Migraine is a common complex neurological disorder involving multiple brain areas that regulate autonomic, affective, cognitive, and sensory functions. This review explores autonomic nervous system (ANS) dysfunction in migraine headache sufferers. Areas covered: Reference material for this review was obtained through PubMed searches. Migraine attacks can present with up to 4 phases (premonitory, aura, headache, postdrome) each with distinguishable signs and symptoms. Altered ANS tone can be found from the prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 94 publications
1
27
0
Order By: Relevance
“…Many features of migraine, such as nausea, vomiting, and thirst, but also cranial autonomic symptoms such as lacrimation, nasal congestion, and rhinorrhea are indicative of altered autonomic function in the central nervous system (CNS) . As such, it has been shown that alterations in sympathetic and parasympathetic tone can be found from the premonitory phase through to postdrome . One proposal is that migraine triggers, such as stress, awakening, or other changes in physiological or emotional homeostasis, activate nociceptive pathways through increased parasympathetic tone .…”
Section: Phase 1: Premonitorymentioning
confidence: 99%
“…Many features of migraine, such as nausea, vomiting, and thirst, but also cranial autonomic symptoms such as lacrimation, nasal congestion, and rhinorrhea are indicative of altered autonomic function in the central nervous system (CNS) . As such, it has been shown that alterations in sympathetic and parasympathetic tone can be found from the premonitory phase through to postdrome . One proposal is that migraine triggers, such as stress, awakening, or other changes in physiological or emotional homeostasis, activate nociceptive pathways through increased parasympathetic tone .…”
Section: Phase 1: Premonitorymentioning
confidence: 99%
“…Therefore, if this important meal is skipped, the neurological system will be deprived of some essential macronutrients and micronutrients (33). As reported in previous studies, hunger has a key role in the incidence of primary headaches (39). In addition, breakfast preparation is an active behavior that involves individuals in social activity (40); through which it might further help in preventing primary headaches.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to CH, dysautonomias also accompany migraine attacks [106]; however, it is too early to comment on any potential effects of DBS on dysautonomias in migraine. (1) DBS of the posterior hypothalamus over time decreases hypothalamic output, decreasing trigeminal sensory neuron excitability.…”
Section: Figurementioning
confidence: 99%